Pengaruh Pemberian Ekstrak Biji Jintan Hitam terhadap Kadar Kolesterol HDL dan LDL Rattus Norvegicus Jantan Galur Wistar yang Diberi Diet Tinggi Lemak - RETNO SETYA KEMALA; CHOESNAN EFFENDI; ASAMI RIETTA KUMALA (HANG TUAH MEDICAL JOURNAL, 2021)
ABTRACT Background: There are a lot of various kinds of plants such as Black Cumin (Nigella sativa L.) which is believed by the people to increase HDL and decrease LDL levels in the blood. The purpose of this experiment to know the effect of extract black cumin seeds (Nigella sativa L.)can increase HDL and decrease LDL cholesterol levels of white rats (Rattus norvegicus). Method: This experiment using 24 of rats which divided into 4 groups, namely the negative control group, positive control group, the treatment group one dosage 126 mg/KgBWand the treatment group two dosage 252 mg/KgBW. This research was carried out for 28 days and continued by termination. Result :In the One way ANOVA test, HDL levels obtained significant values of 0.134 and LDL levels of 0.070 which means p> 0.05 and showed that black cumin seed extract (Nigella sativa L.) there’s no different. Conclusion: black cumin seed extract (Nigella sativa L.) had no effect for increasing HDL and decreasing LDL cholesterol levels of white rats (Rattus norvegicus)